2014
DOI: 10.1002/bit.25442
|View full text |Cite
|
Sign up to set email alerts
|

Efficient hydroxyproline production from glucose in minimal media by Corynebacterium glutamicum

Abstract: The efficient coupling of biotransformation steps to an existing fermentation pathway is an interesting strategy to expand the product portfolio of Corynebacterium glutamicum as whole-cell biocatalyst. This is especially challenging if the biotransformation step comprises a direct link to central metabolism, as in the case of α-ketoglutarate-dependent oxygenase catalysis. Aiming at trans-4-hydroxy-L-proline (Hyp) production from glucose in a minimal medium, the proline-4-hydroxylase gene from Dactylosporangium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 42 publications
0
26
0
1
Order By: Relevance
“…Thet argeted deletion of degrading pathways [13] or an optimization of the reaction conditions (as reported here for 6a)c an be used to circumvent this challenge. Furthermore,i ti sf requently observed in wholecell biotransformations that the fed substrates and products are metabolized by the cellular metabolism.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thet argeted deletion of degrading pathways [13] or an optimization of the reaction conditions (as reported here for 6a)c an be used to circumvent this challenge. Furthermore,i ti sf requently observed in wholecell biotransformations that the fed substrates and products are metabolized by the cellular metabolism.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The previous study indicated that an insufficient supply of DO is an important issue in Hyp fermentation, as it leads to low Hyp yield and the accumulation of acetic acid [11][12][13][14]. Zhao et al [10].…”
Section: Effect Of the Added-protease Fermentation On Hyp Productionmentioning
confidence: 99%
“…In addition, the rate of glucose conversion to Hyp in the APF was 18.1%, while that in CF was 16.7%, which was an increase of 8.4%. Acetic acid is the main metabolic by-product of Hyp production in E. coli, which is generated by metabolic overflow when the oxygen supply is limited [14]. The acetic acid production rate in the APF was obviously lower than that in CF at 18-38 h, and the final concentrations in CF and APF were 4.8 g/L and 2.3 g/L, respectively, which was a decrease of 52.1%, suggesting improvement of oxygen transfer.…”
Section: Effect Of the Added-protease Fermentation On Hyp Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the codon-optimized p4h gene was heterogeneously expressed in four C. glutamicum strains, Hyp production was relatively low (<0.12 g/L; Yi et al, 2014). An isoleucine bradytrophy C. glutamicum strain expressing the p4h gene produced 7.1 g/L of Hyp from glucose by limiting an external isoleucine supply in a fed-batch cultivation (Falcioni et al, 2015). In spite of the high production of L-proline in C. glutamicum (Y.…”
mentioning
confidence: 99%